Juridical Analysis Of Standard Procedure Operational Management And Services (SPOPP) In Making Shari’a Notary Deed Based On Article 15 Paragraph (1) Of Law Number 2 Of 2014 Concerning The Position Of Notary - Mochamad Rizqi Sismanto; Anwar Saleh Hasibuan; Aryani Witasari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study was to: 1) to analyze the implementation of standard operating procedures and service settings (SPOPP) notary in the deed of Shariah is based on article 15 paragraph (1) Law No. 2 of 2014 on the notary office. 2) to analyze the legal consequences shari’a deed made by the notary pursuant to Article 15 paragraph (1) Law No. 2 of 2014 on the notary office. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by qualitative descriptive method.Based on the analysis of data concluded that: 1) the execution of a deed notarized by a notary Shari’ah-based, there are two models in the inclusion of Bismillahhirrohmanirrohim writing. The first one is the inclusion of the article after the title, and the second inclusion Lafadz Bismillahhirromanirrohim/writing there were no written or written and included in the premise. 2) the legal effect of Shariah -based of authentic act by a notary depends on the placement Bissmilahhirrohmanirrohim writing. The first in the inclusion of the text at the beginning of the deed would have violated the rules of the article 38 of Law Notary, that at the beginning consists of the title deed deed, certificate number, full name and place of notary. The second in the inclusion of Bismillahhirrohmanirohim writing something was written and there are included in the premise.Keywords: Notary, Authentic Deed, Bismillahhirrohmanirohim Writing.